Symbolism of the color white in jane Austen’s works - Huỳnh Ngọc Mai Kha; Lê Thị Hồng Nhung (Tạp chí Khoa học và Công nghệ)
The color white's symbolic meaning in Jane Austen's writings reflects a complex portrayal that goes beyond simple beauty. Austen purposefully uses white to represent innocence, purity, and social norms, especially when it comes to how women are portrayed as being morally upright. This study investigates the complex symbolism of white in Austen's stories, focusing on its connections to social norms and moral rectitude. Characters identified with morality and goodness are frequently adorned in white, yet Austen uses this symbolism to discreetly criticize societal conventions and show the contrast between appearances and underlying reality. This analysis reveals the intricate layers of meaning woven within Austen's use of white, providing insight into its symbolic significance within her literary world. The article does this by closely examining every case in which white appears in clothing descriptions, settings, and thematic aspects.